Implementation of Religious Studies to Improve Religious Understanding in the Context of the Pillars of Islam in Qur'anic Education Center Children - Zinu, Mannan; Sulasri, Sulasri; Darmayanti, Darmayanti (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is qualitative research, namely research whose data sources are obtained from observations, interviews, and documentation obtained at the research location and on the objects and samples studied by the author to obtain valid and relevant information on the variables studied, namely in the form of movements, words, and images collected at the research location. Based on the research results, researchers found that: 1) The implementation of religious studies at the Waara Village Qur'anic Education Center (QEC) is routinely carried out every day after the Maghrib prayer, and sometimes continued after the Isha prayer if there are still children who have not had time to recite the Qur'an. The teaching carried out by the teachers starts from the introduction of the Hijayah letters, both pronunciation and makhraj, to children who are still at the Iqro level, as well as learning the laws of tajwid to children who have entered the Qur'an level. 2) The understanding of Islam, in this case understanding and implementing the pillars of Islam in the children of the Waara Village QEC, is quite good. This can be seen from the diligence of the children in performing prayers and fasting during Ramadan, and understanding the sentence of the shahada. This can be consistent because of the affirmation and supervision carried out by the Waara Village QEC teachers, who do not allow their students to learn to recite the Qur'an before performing prayers, and advise them every day before and after carrying out the Qur'an.